Hypoxia-inducible factor prolyl hydroxylase domain (PHD) inhibition after contusive spinal cord injury does not improve locomotor recovery. - George Z Wei; Sujata Saraswat Ohri; Nicolas K Khattar; Adam W Listerman; Catherine H Doyle; Kariena R Andres; Saravanan S Karuppagounder; Rajiv R Ratan; Scott R Whittemore; Michal Hetman (PLoS ONE, 2021)
Traumatic spinal cord injury (SCI) is a devastating neurological condition that involves both primary and secondary tissue loss. Various cytotoxic events including hypoxia, hemorrhage and blood lysis, bioenergetic failure, oxidative stress, endoplasmic reticulum (ER) stress, and neuroinflammation contribute to secondary injury. The HIF prolyl hydroxylase domain (PHD/EGLN) family of proteins are iron-dependent, oxygen-sensing enzymes that regulate the stability of hypoxia inducible factor-1α (HIF-1α) and also mediate oxidative stress caused by free iron liberated from the lysis of blood. PHD inhibition improves outcome after experimental intracerebral hemorrhage (ICH) by reducing activating transcription factor 4 (ATF4)-driven neuronal death. As the ATF4-CHOP (CCAAT-enhancer-binding protein homologous protein) pathway plays a role in the pathogenesis of contusive SCI, we examined the effects of PHD inhibition in a mouse model of moderate T9 contusive SCI in which white matter damage is the primary driver of locomotor dysfunction. Pharmacological inhibition of PHDs using adaptaquin (AQ) moderately lowers acute induction of Atf4 and Chop mRNAs and prevents the acute decline of oligodendrocyte (OL) lineage mRNAs, but does not improve long-term recovery of hindlimb locomotion or increase chronic white matter sparing. Conditional genetic ablation of all three PHD isoenzymes in OLs did not affect Atf4, Chop or OL mRNAs expression levels, locomotor recovery, and white matter sparing after SCI. Hence, PHDs may not be suitable targets to improve outcomes in traumatic CNS pathologies that involve acute white matter injury.